MARVELS OF ADVERTISING:TALES OF TRIUMPH OF THE MOST BUZZING ADVERTISING WORDS IN 2022 - Singh Sethi, Dr. Amanjeet; Bisht, Dr. Vaishali; Singh Bisht, Dr. Bhaskar; Singh, Jaskaran (The journal of contemporary issues in business and government, 2023)
Advertising means a company's planning to reach their present/future clients and unique advertising is a method that can imaginatively share the company’s narrative to encourage and enhance sales. Buzz marketing is a modern-day marketing method that accord importance to magnify the potentiality of an ad campaign or merchandise. Buzzing words involves locating and involving key words to create buzz and eagerness about a good or service. The main role of buzzing advertising words is to spread the advertising message quickly among the customers. This paper makes an effort to study the buzzing words, current scenario and predominant causes in relation to the spread of this marketing strategy in the business world. In the end, this paper ratiocinate that such type of marketing strategy has the potential to increase the speed of the advertising message to the end consumers and also to increase the sales of the brand but still many aspects have to be considered before this strategy becomes a viable option for business world.